2020
DOI: 10.47059/alinteri/v35i2/ajas20089
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Gold Nanoparticles Using Pomegranate Peel Extract and Its Antioxidant and Anticancer Activity against Liver Cancer Cell Line

Abstract: Decrease of gold metal particles in contact with the watery strip concentrate of pomegranate organic product finishes the bio-union of gold nanoparticles. At the frequency scope of 350-700nm, an assimilation pinnacle of the biosynthesized gold nanoparticles is noticed. At 530nm, the UV-Visible range of gold nanoparticles orchestrated by pomegranate strip remove shows most extreme pinnacle assimilation. SEM has contemplated the morphological qualities of gold nanoparticles, affirming the round type of gold nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…For instance, Elumalai and Velmurugan [98] indicated that the antimicrobial activity of ZnONPs against S. aureus, B. subtilis, P. aeruginosa, P. mirabilis, E. coli, C. albicans and C. tropicalis increased with increasing ZnONPs concentrations. Also, Rajeshkumar et al [99] reported that ZnONPs exhibited substantial antibacterial, antifungal and antioxidant activities opon increasing their concentrations. In addition, Sumanth et al [100] confirmed that ZnONPs produced by Xylaria acuta could proficiently exhibited antimicrobial and anticancer activities in a dose dependent manner.…”
Section: Concentration Of Znonpsmentioning
confidence: 99%
“…For instance, Elumalai and Velmurugan [98] indicated that the antimicrobial activity of ZnONPs against S. aureus, B. subtilis, P. aeruginosa, P. mirabilis, E. coli, C. albicans and C. tropicalis increased with increasing ZnONPs concentrations. Also, Rajeshkumar et al [99] reported that ZnONPs exhibited substantial antibacterial, antifungal and antioxidant activities opon increasing their concentrations. In addition, Sumanth et al [100] confirmed that ZnONPs produced by Xylaria acuta could proficiently exhibited antimicrobial and anticancer activities in a dose dependent manner.…”
Section: Concentration Of Znonpsmentioning
confidence: 99%
“…Thus, they possess anticancer. Because other types have been reported to contain anticancer bioactive compounds, more research should be conducted to determine the potential of E. indica as a source of anticancer bioactive compounds [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro cytotoxic effects of copper nanoparticles synthesized from avocado seed extract [12], Green synthesis of copper oxide nanoparticles using tamarind extract and its alpha-amylase inhibitory activity [13], cytotoxic activity study of copper oxide nanoparticle mediated through tamarind extract [14]. Our team has extensive knowledge and research experience that has been translated into high quality publications [15 -20].…”
Section: Manymentioning
confidence: 99%